Pesantren Dan Perubahan Sosial: Studi Terhadap Peran Pesantren Al-Ishlah, Sidamulya Cirebon - Ahmad Dzikri Dzikri (Institut Agama Islam Negeri Padangsidimpuan, 2019)
da'wah in Indonesia. In addition, Islamic boarding schools are defined as sustainable ritual institutions, moral development institutions, as covering Islamic Education. It is also as social institutions that have experienced various life variations; which is adjusted to the burden of growth of the community in the midst of the pesantren. This research is intended to describe the history and the social changes of the communities of the Al-Ishlah Sidamulya Astanajapura Cirebon Islamic Boarding School. It is also to describe the role of the Boarding School in fostering the lives of the community around the pesantren. This study uses historical history studies. The results of this study indicated that the Al-Ishlah Sidamulya Islamic Boarding School is one of the pesantren which has an important role in matters relating to the Sidamulya community; in religious, educational, social and economic fields of the communities. The social changes happen in the communities are malima activity (the thief, main, madat, mabok, madon) changed to salima (shubuh, dhuhur, ashar, maghrib and isya). In addition, planting the values of Islam to show the real Muslim through routine tarikat (Tijaniyah), activities of manakiban, tahlilan and tadarrusan.